2018
DOI: 10.1002/pts.2388
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the diffusional behaviour of Irganox®1076 antioxidant in HDPE/Cloisite®15A nanocomposite‐based food contact packaging films: Effect of nanoclay loading

Abstract: In this research work, the prediction of the diffusion coefficient (Dp) of Irganox® 1076 (Ir‐76) antioxidant in HDPE‐based food contact packaging films was carried out. The diffusion of this additive was studied both, in neat HDPE film and in HDPE nanocomposites films made of HDPE matrix filled with 1, 3, and 5 wt% of a commercially available organoclay (Cloisite®15A). The diffusion experiments were carried out by using the Roe's method on films consisting of a stack of several polymer films having a total nom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The laminate film reduced permeability to CO 2 by more than one order of magnitude and reduced H 2 S permeability to an undetectable level. Cherif et al [167] studied the diffusion behavior of Irganox ® 1076 antioxidant (BASF, Ludwigshafen, Germany) in a novel food contact packaging film consisting of high-density polyethylene (HDPE)/cloisite ® 15A (BYK Additives & Instrument, Wesel, Germany) nanoclay composites. The diffusion coefficients were determined according to Fick's law, which showed that the maximum diffusion rate reduction of the antioxidant reached 78% with a three wt% nanoclay loading.…”
Section: Food Packagingmentioning
confidence: 99%
“…The laminate film reduced permeability to CO 2 by more than one order of magnitude and reduced H 2 S permeability to an undetectable level. Cherif et al [167] studied the diffusion behavior of Irganox ® 1076 antioxidant (BASF, Ludwigshafen, Germany) in a novel food contact packaging film consisting of high-density polyethylene (HDPE)/cloisite ® 15A (BYK Additives & Instrument, Wesel, Germany) nanoclay composites. The diffusion coefficients were determined according to Fick's law, which showed that the maximum diffusion rate reduction of the antioxidant reached 78% with a three wt% nanoclay loading.…”
Section: Food Packagingmentioning
confidence: 99%
“…Ait cherif et al 45 also found activation energies of 103.12 and 117.05 kJ mol −1 for D p in the HDPE and HDPE/C15A, respectively, thus confirming that the incorporation of nanofillers slow down the diffusion of molecular additives.…”
Section: Resultsmentioning
confidence: 85%
“…All these results are consistent with the expected improvements and the literature data. As an example, the diffusion of Irganox 1076 in HDPE/C15A was studied by Ait cherif et al 45 using FTIR spectroscopy. Values of D p of 9.0 × 10 −11 and 7.8 × 10 −10 cm 2 s −1 were obtained at 80 and 100°C, respectively, for HDPE filled with 3 wt% of nanoclays.…”
Section: Resultsmentioning
confidence: 99%
“…TEM and XRD investigations on PLA/EVA blend nanocomposites were carried out to reveal the clay dispersion, exfoliation/intercalation states and its partition in the blend phases, as main controlling factors, which affect gas barrier properties of the final system. [38] The TEM micrographs of PLA/EVA (75/25) blend nanocomposites in the presence and absence of compatibilizer are depicted in Figure 4a,b. Combination of mainly intercalated and some exfoliated structures are seen in both the systems confirmed by XRD analysis too (Figure 4c).…”
Section: (4 Of 10)mentioning
confidence: 99%